How do I write the Laurent series for $\frac{1}{z^2(z-i)}$ for $1<|z-1|<\sqrt2$?

I know that I need to rewrite it somehow to fit the geometric series form of $\frac{1}{1-r}$, but I'm stuck on getting here. I'm also aware that $z_0=1$, so then my "r" should have $z-1$ in it correct? After that I think I can do the rest from there.


I know that I need to rewrite it somehow to fit the geometric series form of $\frac{1}{1-r}$, but I'm stuck on getting here.

If you know already that you should use partial fractions, then you can jump to Equation $(2)$ and from there on. In B. and C. the geometric series you need are indicated and motivated, I hope.

I'm also aware that $z_0=1$, so then my "r" should have $z-1$ in it correct?


A. When the given function is of the form $f(z)=\frac{p(z)}{q(z)}$, with $p(z)$ and $q(z)$ being polynomials in $z$, the first step is to expand it into partial fractions. Due to the form of $f(z)$ this means that

\begin{equation} f(z)\equiv \frac{1}{z^{2}\left( z-i\right) }=\frac{A}{z^{2}}+\frac{B}{z}+\frac{C}{z-i}. \tag{1} \end{equation}

To find the coefficients we can use the Heaviside cover-up method.

  • To determine $C$, multiply by $\left( z-i\right) $ and use the root $z=i$ of the denominator $q(z)= z^{2}\left( z-i\right)$ and evaluate the limit \begin{equation*} C=\lim_{z\rightarrow i}f(z)\left( z-i\right) =\lim_{z\rightarrow i}\frac{1}{z^{2}}=\frac{1}{i^{2}}=-1. \end{equation*}

  • To find $A$, multiply by $z^{2}$ and use the root $z=0$ of $q(z)$: \begin{equation*} A=\lim_{z\rightarrow 0}f(z)z^{2}=\lim_{z\rightarrow 0}\frac{1}{z-i}=i. \end{equation*}

  • To determine $B$, substitute $C$ and $A$ in one of the equations resulting from $(1)$ after being multiplied by $\left( z-i\right) $ or $z^{2}$ , and pick a meaningful $z$, e.g. $z=1$: \begin{equation} f(z)\left( z-i\right) =\frac{1}{z^{2}}=\frac{A}{z^{2}}\left( z-i\right) +\frac{B}{z}\left( z-i\right) +C, \end{equation}

\begin{equation} z=1\implies 1=i\left( 1-i\right) +B\left( 1-i\right) -1\implies B=1. \end{equation}


\begin{equation} f(z)\equiv \frac{1}{z^{2}\left( z-i\right) }=\frac{i}{z^{2}}+\frac{1}{z}- \frac{1}{z-i}. \tag{2} \end{equation}

B. To make some algebraic manipulations easier we now use the substitution $w=z-1$. Then the annulus $1<\left\vert z-1\right\vert <\sqrt{2}$ becomes the new annulus $1<\left\vert w\right\vert <\sqrt{2}$, centered at $w=0$, and $\frac{1}{z^{2}\left( z-i\right) }$ becomes

\begin{equation} \frac{1}{z^{2}\left( z-i\right) }=\frac{1}{\left( w+1\right) ^{2}\left[ w+\left( 1-i\right) \right] }\equiv g(w). \tag{3} \end{equation}

By $(2)$ the function $g(w)$ can be expanded as

\begin{equation} g(w)=\frac{1}{w+1}+\frac{i}{\left( w+1\right) ^{2}}-\frac{1}{w+\left( 1-i\right) }. \tag{4} \end{equation}

C. Each term can be expanded into a particular geometric series as follows:

  1. For $\color{blue}{1<\left\vert w\right\vert }$ and using the sum of the complex geometric series $\displaystyle\sum_{n\geq 0}\dfrac{\left( -1\right) ^{n}}{w^{n}}=\frac{1}{1-\left(-1/w\right) }$, the first term can be written as \begin{equation*} g_{1}(w)\equiv \frac{1}{w+1}=\frac{1}{w}\frac{1}{1+1/w}=\frac{1}{w}\frac{1}{ 1-\left( -1/w\right) } \end{equation*} and expanded into \begin{equation} g_{1}(w)=\frac{1}{w}\sum_{n\geq 0}\frac{\left( -1\right) ^{n}}{w^{n}} =\sum_{n\geq 0}\frac{\left( -1\right) ^{n}}{w^{n+1}}, \text{ for } \color{blue}{1<\left\vert w\right\vert} . \tag{5} \end{equation}
  2. As for the second term, for $\color{blue}{\left\vert w\right\vert >1}$ as well, since $$\frac{1}{\left( w+1\right) ^{2}}=-\frac{d}{dw}\left( \frac{1}{w+1}\right) =-\frac{d}{dw}g_{1}(w),$$ it can be expanded into \begin{align} g_{2}(w) &\equiv \frac{i}{\left( w+1\right) ^{2}}=-i\frac{d}{dw}g_{1}(w)=-i\frac{d}{dw}\sum_{n\geq 0}\frac{\left( -1\right) ^{n}}{w^{n+1}} \\ &=i\sum_{n\geq 0}\left( -1\right) ^{n}\frac{n+1}{w^{n+2}}=-i\sum_{n\geq 1}\left( -1\right) ^{n}\frac{n}{w^{n+1}},\text{ for }\color{blue}{1<\left\vert w\right\vert }. \tag{6} \end{align}
  3. As for the third term, if $\left\vert - \dfrac{w}{1-i}\right\vert =\color{green}{\dfrac{\left\vert w\right\vert }{\sqrt{2}}<1}$, we have that \begin{align} g_{3}(w) &\equiv \frac{1}{w+\left( 1-i\right) }=\frac{1}{1-i}\frac{1}{1-\left( -\frac{w}{1-i}\right) } \\ &=\frac{1}{1-i}\sum_{n\geq 0}\frac{\left( -1\right) ^{n}w^{n}}{\left( 1-i\right) ^{n}}=\sum_{n\geq 0}\frac{\left( -1\right) ^{n}w^{n}}{\left(1-i\right) ^{n+1}}\text{ for }\color{green}{\left\vert w\right\vert <\sqrt{2}}. \tag{7} \end{align}

D. From $(5)-(7)$ it follows that for $\color{blue}{1<}\left\vert w\right\vert \color{green}{<\sqrt{2}}, $

\begin{align} g(w) &=g_{1}(w)+g_{2}(w)+g_{3}(w) \\ &=\sum_{n\geq 0}\left( -1\right) ^{n}\left[ \frac{1-in}{w^{n+1}}+\frac{w^{n}}{\left( 1-i\right) ^{n+1}}\right] \text{ for }\color{blue}{1<}\left\vert w\right\vert \color{green}{<\sqrt{2}}. \tag{8} \end{align}

In terms of the given function $f(z)$, we thus have the following expansion for $\color{blue}{1<}\left\vert z-1\right\vert \color{green}{<\sqrt{2}} $:

\begin{equation} f(z)=\sum_{n\geq 0}\left( -1\right) ^{n}\left[ \frac{1-in}{\left( z-1\right) ^{n+1}}+\frac{\left( z-1\right) ^{n}}{\left( 1-i\right) ^{n+1}}\right] \text{ for }\color{blue}{1<}\left\vert z-1\right\vert \color{green}{<\sqrt{2}} . \tag{9} \end{equation}


First of all, you should do use the fact that$$\frac1{z^2(z-i)}=\frac i{z^2}-\frac1{z-i}+\frac1z.$$So, if $|z-1|>1$, \begin{align}\frac1z&=\frac1{1+(z-1)}\\&=-\sum_{n=-\infty}^{-1}(-1)^n(z-1)^n.\end{align}It follows from this that\begin{align}\frac1{z^2}&=-\left(\frac1z\right)'\\&=-\left(\sum_{n=-\infty}^{-1}(-1)^n(z-1)^n\right)'\\&=-\sum_{n=-\infty}^{-1}n(-1)^n(z-1)^{n-1}\\&=\sum_{n=-\infty}^{-2}(n+1)(-1)^n(z-1)^n.\end{align}On the other hand, if $|z-1|<\sqrt2$, then\begin{align}-\frac1{z-i}&=\frac1{i-z}\\&=\frac1{-1+i-(z-1)}\\&=\frac1{-1+i}\sum_{n=0}^\infty\frac{(z-1)^n}{(-1+i)^n}\\&=\sum_{n=0}^\infty\frac{(z-i)^n}{(-1+i)^{n+1}}.\end{align}So, all that remains to be done is to put these three series together.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.